Comparative efficacy of materials used in patients undergoing pulpotomy or direct pulp capping in carious teeth: A systematic review and meta‐analysis - Athanasios Fasoulas; Georgios Keratiotis; Loukia Spineli; Nikos Pandis; Mieke A. A. De Bruyne; Roeland J.G. De Moor; Maarten A. Meire (Wiley, 2023)
Abstract Objectives Different materials have been used for capping the pulp after exposure during caries removal in permanent teeth. The purpose of this study was to collate and analyze all pertinent evidence from randomized controlled trials (RCTs) on different materials used in patients undergoing pulpotomy or direct pulp capping in carious teeth. Materials and Methods Trials comparing two or more capping agents used for direct pulp capping (DPC) or pulpotomy were considered eligible. An electronic search of four databases and two clinical trial registries was carried out up to February 28, 2021 using a search strategy properly adapted to the PICO framework. Screening, data extraction, and risk of bias (RoB) assessment of primary studies were performed in duplicate and independently. The primary outcome was clinical and radiological success; secondary outcomes included continued root formation, tooth discoloration, and dentin bridge formation. Results 21 RCTs were included in the study. The RoB assessment indicated a moderate risk among the studies. Due to significant clinical and statistical heterogeneity among the studies, performing network meta‐analysis (NMA) was not possible. An ad hoc subgroup analysis revealed strong evidence of a higher success of DPC with Mineral Trioxide Aggregate (MTA) compared to calcium hydroxide (CH) (odds ratio [OR] = 3.10, 95% confidence interval [CI]: 1.66−5.79). MTA performed better than CH in pulp capping (both DPC and pulpotomy) of mature compared to immature teeth (OR = 3.34, 95% CI: 1.81−6.17). The GRADE assessment revealed moderate strength of evidence for DPC and mature teeth, and low to very low strength of evidence for the remaining subgroups. Conclusions Considerable clinical and statistical heterogeneity among the trials did not allow NMA. The ad hoc subgroup analysis indicated that the clinical and radiographic success of MTA was higher than that of CH but only in mature teeth and DPC cases where the strength of evidence was moderate. PROSPERO Registration: number CRD42020127239.